Equilibrium and kinetic studies of metallic ions and residual oil removal from palm oil mill effluent using natural zeolite - Shavandi, Mohammad Amin (2012)
The removal of heavy metals (Fe, Zn and Mn) and residual oil from palm oil mill effluent using natural zeolite was studied in this research. In order to evaluate the effectiveness of natural zeolite as a low cost and abundant adsorbent, different laboratory experiments were performed, including batch studies, desorption studies,equilibrium and kinetic tests, and column studies. Equilibrium studies show that, pH plays a major role in removal of both heavy metal and residual oil. Uptake of the tested heavy metals increased with pH and maximum removal was observed at pH 6.0, while maximum residual oil was removed at pH 3.0. Equilibrium data obtained from metal removal and oil removal followed the Langmuir and Freundlich isotherm models respectively while the kinetic data of both metal ions and oil removal were well described by the pseudo-second-order equation. The results obtained demonstrated that up to 70% of residual oil along with more than 50% of Zn(II) and Mn(II) and about 60% of Fe(III) could be removed by natural zeolite in the experiments. Column studies results also indicated that natural zeolite can be used for oil and heavy metal removal from flowing POME. The time of breakthrough increased with a higher bed depth and slower flow rate. The Bohart and Adams model and the bed depth service time model (BDST) were used to estimate the experimental data.